Rural tourism in Northern Portugal – Motivations and barriers - Castro, Conceição (RITUR - Revista Iberoamericana de Turismo, 2019)
Tourism in rural areas boosts economic dynamism, turning them more attractive, diversifying economic activities, creating jobs and wealth. With the importance that micro and small firms play on economic growth, particularly in rural areas, the objective of this article is to analyze the main motivations to start a business in rural tourism and the problems and barriers faced by these entrepreneurs in Northern Portugal. With the results of a survey an exploratory factor analysis was conducted to distinguish underlying motivational structures and the results suggested that the main motivations to create the business were related to family and success. Using cluster analysis owners were grouped into three segments. They encountered some restrictions in the start-up process as bureaucracy, lack of financial support and information.